2008
DOI: 10.1002/j.2161-0045.2008.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Issues of Stability and Change in Interest Development

Abstract: Interest development is not an easily studied process. There are at least 4 methods for examining the process of stability and change over time: relative stability, absolute stability, profile stability, and structural stability. A program of research that focuses on examining these 4 types of stability is summarized relative to the issues pertinent to the development of vocational interests in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 42 publications
0
38
0
6
Order By: Relevance
“…Some have argued that stability of interests over time is very low in children younger than age 12 (Low, Yoon, Roberts, & Rounds, 2005). Others have found that interests do show moderate levels of stability during the late elementary school years (Tracey, 2002; Tracey & Sodano, 2008; Tracey & Ward, 1998). Our data reveal that this stability may be evident much earlier than previous studies have demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Some have argued that stability of interests over time is very low in children younger than age 12 (Low, Yoon, Roberts, & Rounds, 2005). Others have found that interests do show moderate levels of stability during the late elementary school years (Tracey, 2002; Tracey & Sodano, 2008; Tracey & Ward, 1998). Our data reveal that this stability may be evident much earlier than previous studies have demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Although a high short-term stability for hunting and fishing interests have been found (Hansen & Sullard, 2002), research on the influence of marriage and parenthood indicates that these events increase the extent to which leisure behavior is performed at home (and that young females more than young men decrease or drop leisure activities; reviewed by Raymore, Barber, & Eccles, 2001). However, in childhood and early adolescence, absolute stability of interest scores very often increase (Tracey & Sodano, 2008), a finding of importance to the fact that starting hunting at a young age leads to a more permanent hunting interest, compared with a later initiation into hunting. The existence of both change and stability of interests from childhood to adulthood obviously should be considered when recruitment to hunting is studied.…”
Section: Stability Of Interest and Identity Formationmentioning
confidence: 92%
“…Schultheiss comments that there is a lack of detailed research on children's career development that is founded on theory. Tracey and Sodano's (2008) article demonstrates how career research of children can provide support for theoretical conceptualizations, such as Holland's (1997) view of vocational interests. Porfeli et al express other concerns about the extant theoretical frameworks that inform research and practice, pointing to the lack of consistent operational definitions of career constructs and the consequent threat this creates in terms of the validity of research findings and career interventions.…”
Section: September 2008 • Volume 57mentioning
confidence: 97%
“…This concept suggests the expansion of the boundaries of career exploration rather than a narrowing down of options (such as occupational gender stereotyping) at a developmental stage when such expansion is developmentally more appropriate career behavior. A further example of embedding research findings in conceptual frameworks is found in the long-term research program of Tracey and his colleagues (Tracey, & Darcy, 2002;Tracey, Lent, Brown, Soresi, & Nota, 2006;Tracey, Robbins, & Hofsess, 2005;Tracey & Rounds, 1993;Tracey & Sodano, 2008;Tracey & Ward, 1998). Tracey and Sodano's review of this program of research provides an excellent example of how such research can be conceptualized within a framework that defines the process of interest stability and change over time.…”
mentioning
confidence: 99%